Prospects and policies for global food security - Breisinger, Clemens (2016)
Presented by IFPRI Senior Research Fellow Clemens Breisinger, at BioVisionAlexandria 2016, April 12, 2016. For more information, please visit: www.egyptssp.ifpri.info